Carbon dioxide adsorption in microwave-synthesized metal organic framework CPM-5: Equilibrium and kinetics study - Sabouni, Rana (2013)
The adsorption equilibrium and diffusion of CO2 in CPM-5 (crystalline porous materials) were experimentally studied using a volumetric approach at three different temperatures 273, 298, and 318 K and gas pressures up to 105 kPa. The Freundlich adsorption equilibrium model was applied to correlate the adsorption isotherms, and the classical microspore diffusion model was applied to obtain the adsorption kinetic curves and diffusivity of CO2 in CPM-5. The selectivity of CO2 over N2 was estimated from the single component isotherms at conditions relevant to post combustion applications (0.15 bar PCO2 and 0.75 bar pN2). It was found that at pressures up to 105 kPa, the CPM-5 adsorbent has CO2 adsorption capacity of 3 mmol/g, 2.3 mmol/g, at 273 K and 298 K, respectively, which is significantly higher than those of MOF-5 under the same conditions. The selectivity factor was 14.2 and 16.1 at 273 and 298 K, respectively. The CO2 diffusivity in CPM-5, estimated from the adsorption kinetic data measured at low pressures, are 1.86 × 10-12 m2/s, 7.04 × 10-12 m2/s, and 7.87 × 10-12 m2/s at 273 K, 298 K and 318 K, respectively. The initial isosteric heat of adsorption of CO2 on the CPM-5 is 36.1 kJ/mol. CPM-5 shows attractive adsorption properties as an adsorbent for separation of CO2 from flue gas.